PROYECTO DE FACTIBILIDAD PARA LA CREACIÓN DE UNA CAJA DE AHORRO A LA PARROQUIA YANGANA DEL CANTÓN Y PROVINCIA DE LOJA - Barrera Espinosa, Astrid Carolina (2016)
The development of this research work, discusses the feasibility study for the creation of a savings bank in the canton Yangana and Loja Province "parish, the project consists of four specific objectives such as market research, technical, financial , Administrative and Financial Officer. First, a market study was carried out to determine the acceptability of the savings bank in the sector, and financial products and services it will offer. This study could define the current and future demand, it should be emphasized that there is an unmet demand for 377 people, making it a convenient place project development. The second objective was to determine through a technical study the location, size and other elements required for the installation and operation of the Savings and Credit, managing to establish the location and size of the entity. The third objective is for study conduct the administrative and legal framework for the implementation of the project. In this study the organizational structure of the Investment Savings indicated Segura In which the roles and responsibilities of personnel work was determined that an administrative manual for indicating each of the activities that must be met for the efficient functioning of the entity was designed. 6 A final objective is to make the Economic and Financial study to determine the total project investment, fixed costs, revenue, funding necessary for the implementation of this project and profitability. Study on Financial Investment total fixed assets both, deferred assets, working capital and obtaining a total investment of $ 5.091,09 are summarized; Economic Assessment on the cash flows of $ 812.24 were determined finally the study of financial indicators was performed as Net Present Value is $ 7.714,62which is positive and means that the project is feasible, the internal rate of return is 64,37% which is also favorable result, Benefit Cost Ratio is 1.82 cents., which indicates that for every dollar invested 0.23 CTV won. Regarding the Recovery of Capital is able to meet the investment will be recovered within 1 year, 4 months and 20 days, these results prove the feasibility of the project and may run. For the development of this thesis methods and techniques such as the use of theoretical contents where the subject of study deepened it was applied as well as the survey that thanks to this it was possible to meet the needs of the parish and through this conduct the necessary studies to determine the economic viability of the project. Finally you can make the respective findings and recommendations based on the study and proposal made